1998
DOI: 10.3354/ame014171
|View full text |Cite
|
Sign up to set email alerts
|

Diel fluctuations in rates of CO2 evolution from standing dead leaf litter of the emergent macrophyte Juncus effusus

Abstract: Standing dead plant litter of emergent macrophytes often forms a considerable portion of the detrital mass in wetland habitats. We examined the effects of varying environmental conditions on the die1 respiratory activity (rate of CO2 evolution) of microbial assemblages associated with standing dead litter of the emergent macrophyte Juncus effusus L. from a small freshwater wetland in central Alabama, USA. Availability of water was a major factor affecting rates of respiration in standing litter. Under field co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 38 publications
(60 reference statements)
7
34
1
2
Order By: Relevance
“…Recently, researchers have shown that it is likely that in general fungi dominate secondary microbial production in marine and freshwater standing decaying grass shoots (26,27,37,46,50,53). Kohlmeyer et al (25) found a diverse community of ascomycetous decomposers that are especially adapted to standing decaying blades of black needlerush (J. roemerianus).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have shown that it is likely that in general fungi dominate secondary microbial production in marine and freshwater standing decaying grass shoots (26,27,37,46,50,53). Kohlmeyer et al (25) found a diverse community of ascomycetous decomposers that are especially adapted to standing decaying blades of black needlerush (J. roemerianus).…”
Section: Discussionmentioning
confidence: 99%
“…Dew is also an important wetting phenomenon for standing-decaying blades of freshwater macrophytes (Kuehn & Suberkropp 1998b). Since there would not appear to be a difference in dew formation between adjacent freshwater marsh and saltmarsh ecosystems, the limitation of fungi in freshwater leaves may be a consequence of response of particular types of decaying blades to dewset.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, large amounts of dead plant matter remain standing within wetland habitats (Findlay et al 1990, Lee 1990, Wetzel & Howe 1999, and are colonized and decomposed in an upright aerial position (Newell 1993, Newell et al 1995, Bärlocher & Biddiscombe 1996, Kuehn & Suberkropp 1998a,b Kuehn et al. 1999, Gessner 2000b.…”
Section: Abstract: Litter Decomposition · Phragmites Australis · Wetmentioning
confidence: 99%